Solid-phase extraction of chromium(iii) with an ion-imprinted functionalized attapulgite sorbent prepared by a surface imprinting technique. Issue 21 (23rd May 2017) - Li, Zhenhua; Kou, Wei; Wu, Shang; Wu, Lan
Abstract : A new chromium(iii )-imprinted azodicarbonamide-functionalized attapulgite sorbent was synthesized by a surface imprinting technique and was employed as a selective solid-phase extraction material for speciation analysis of chromium(iii ) in environmental water samples prior to its determination by inductively coupled plasma atomic emission spectrometry (ICP-AES). Abstract : A new chromium(iii )-imprinted azodicarbonamide-functionalized attapulgite sorbent was synthesized by a surface imprinting technique and was employed as a selective solid-phase extraction material for speciation analysis of chromium(iii ) in environmental water samples prior to its determination by inductively coupled plasma atomic emission spectrometry (ICP-AES). The experimental conditions for the effective adsorption of Cr(iii ) were optimized with respect to different experimental parameters using static and dynamic procedures in detail. Compared with non-imprinted sorbent particles, the ion-imprinted sorbents had higher selectivity and adsorption capacity for Cr(iii ). The maximum static adsorption capacity of the ion-imprinted and non-imprinted sorbents for Cr(iii ) was 69.75 and 21.06 mg g −1, respectively. The relative selectivity factor values ( α r ) of Cr(iii )/Pb(ii ), Cr(iii )/Cu(ii ), Cr(iii )/Ni(ii ), Cr(iii )/Sb(iii ), Cr(iii )/As(iii ) and Cr(iii )/Fe(iii ) were 55.46, 49.52, 44.53, 49.24, 41.77, and 26.63 respectively, which were greater than 1. The imprinted attapulgite sorbent offered fast kinetics for the adsorption and desorption of Cr(iii ). Under the optimized conditions (pH – 5.0, mass – 30 mg, shaking time – 20 min), a detection limit of 0.25 ng mL −1 with a relative standard deviation (RSD) of 2.4% for Cr(iii ) was obtained. The method has been validated by analyzing certified reference materials and successfully applied to the determination of trace Cr(iii ) in environmental samples.